Counter-hegemonic networks and the transformation of global climate politics: rethinking movement-state relations. Issue 2 (3rd July 2014) - Smith,
Abstract : Global financial and ecological crises have fueled the diffusion of ideas and discourses that challenge US hegemony and global capitalism and support the expansion of counter-hegemonic alliances between states and social movements. Social movements are calling for rights for Mother Earth and for the development of new measures of well-being, putting forward increasingly credible alternatives to the state-led, market-based approaches to reducing greenhouse gas emissions. This paper traces the social movement processes that have advanced ecological and social justice critiques of capitalist development. It explores how regional and global networks of states and movements have contributed to the growing political salience of new claims and discourses that respond to the ecological threats posed by global warming. These observations reveal how social movement challenges contribute to an expanding realm of global politics that transgresses the traditional boundaries of the inter-state arena, calling for adaptations to our theoretical frameworks for understanding global social change.